2010
DOI: 10.1115/1.4000364
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Long-Term Performance of Steels T91 and 316L in Oxygen-Containing Flowing Lead-Bismuth Eutectic at 550°C

Abstract: The long-term performance of ferritic/martensitic steel T91 and austenitic 316L in oxygen-containing flowing lead-bismuth eutectic at 550°C was investigated by exposing the materials for up to 15,000 h in the CORRIDA loop. The velocity of the liquid-metal flow was 2 m/s and the concentration of dissolved oxygen averaged 1.6×10−6 mass %. The resulting corrosion processes and products were analyzed and quantified using metallographic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…Previous studies in the literature [7][8][9][10][11][12][13][14][15] have shown similar behavior in LBE for the same type of alloys and test conditions, and thus the presented results were expected. Although both alloys were attacked by liquid lead, the magnitudes of the attacks were different.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous studies in the literature [7][8][9][10][11][12][13][14][15] have shown similar behavior in LBE for the same type of alloys and test conditions, and thus the presented results were expected. Although both alloys were attacked by liquid lead, the magnitudes of the attacks were different.…”
Section: Discussionsupporting
confidence: 82%
“…The predominant issue when designing LFR systems is the choice of corrosion resistant steels [5,6]. Liquid lead and lead bismuth eutectic (LBE) attacks structural steels, such as AISI 316L and 15-15 Ti at temperatures in excess of 500°C, thus limiting the operation temperature of the reactor [7][8][9][10][11][12][13][14][15]. Alumina forming FeCrAl alloys have been proposed as a promising solution, both as bulk steels [5,[16][17][18][19][20][21][22] and more recently through surface alloying [8,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In both cases the near-surface zone of the steel does not show depletion in steel constituents beyond the corrosion front. Similar corrosion appearances were observed in LBE with 10 À6 mass% dissolved oxygen, but as a result of local failure of spinel layer (AO), representing general corrosion mode, or Cr-based oxide film (PS) [5,17,18]. Both, selective and non-selective leaching are governed by the transport of solved elements in the boundary layer and subsequent transfer to the liquid metal bulk [6].…”
Section: Corrosion Appearances Observedmentioning
confidence: 82%
“…At 10 À6 mass% dissolved oxygen, the austenitic steels mostly show AO accompanied by spinel formation [5,17,18]. With time, after local failure of scale, a local SBA via selective leaching occurs.…”
Section: Introductionmentioning
confidence: 99%
“…at the interface with LBE and steel, respectively. Some oxide has penetrated the steel along grain boundaries, but, in contrast to the performance of the same material at higher temperature [26,36], an important internal oxidation zone has not developed underneath the spinel layer. The spinel layer itself has a layered sub-structure with local Cr-enrichment especially at the spinel/steel interface (Fig.…”
Section: Evaluation Of the Quantitative Measurementsmentioning
confidence: 88%